2015
DOI: 10.1016/j.kjms.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of P‐glycoprotein overexpression by Ginkgo biloba extract in the brains of pentylenetetrazole‐kindled and phenytoin‐treated mice

Abstract: The purpose of this study was to investigate the combined effects of Ginkgo biloba extract and phenytoin (PHT) sodium as a dose regimen simulating the clinical treatment of patients with epilepsy, on P-glycoprotein (P-GP) overexpression in a pentylenetetrazole-kindled mouse model of epilepsy. Epilepsy was induced by intraperitoneal administration of pentylenetetrazole (40 mg/kg) for 7 days followed by intragastric administration of PHT (40 mg/kg) for 14 days. Thirty mice that developed seizures were randomly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…In the present study, repeated administration of verapamil, aged garlic, and ginkgo biloba extracts for 14 days showed a significant impact on P-gp expression, either upregulation (for aged garlic) or downregulation (for verapamil and ginkgo biloba). These findings are in line with previous studies that examined the intestinal P-gp expression following repeated dose administration of aged garlic extract (Hajda et al, 2010) and ginkgo biloba extract (Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, repeated administration of verapamil, aged garlic, and ginkgo biloba extracts for 14 days showed a significant impact on P-gp expression, either upregulation (for aged garlic) or downregulation (for verapamil and ginkgo biloba). These findings are in line with previous studies that examined the intestinal P-gp expression following repeated dose administration of aged garlic extract (Hajda et al, 2010) and ginkgo biloba extract (Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…(2015) who found that administration of different dosages of phenobarbital resulted in decreased number of Bcl-2 positive cells and increased number of cells positive for Bax in the brain of rats compared with those of the control group. Intragastric administration of phenytoin in epileptic mice resulted in increased expression of Caspase-3 in both the hippocampal and cortical region (Zhang et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As stated earlier, the LLOQ for phenytoin and 4-HPPH in this study was 7.81 ng/mL for plasma and 23.4 ng/g for brain tissue showing that the assay has ample range to detect lower concentrations in future studies of other phenytoin intranasal delivery systems, if necessary. For comparison, the sensitivity of previously reported methods for phenytoin (and occasionally 4-HPPH) measurement in rat plasma or brain have been restricted to lower limits of quantification between 50 and 500 ng/mL, as these studies have generally dealt with typical systemic doses of phenytoin which produce high plasma and brain concentrations [5,9,[23][24][25]46].…”
Section: Application Of the Lc-ms/ms Methods To The Study Of Intranas...mentioning
confidence: 99%